BUILD UNDERSTANDING STUDENT ABOUT METHOD WORK LUNGS THROUGH PROJECT-BASED EXPERIMENTS AT SDN 188 PEKANBARU - Mutiara Putri; Dhiva Meisa Aryenda; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Science education at the elementary school level has an important role in shaping scientific thinking and improving students' understanding of natural concepts, one of which is the human respiratory system. In this case, the lungs become organ vital Which worthy introduced through method interesting and applicable learning. This study aims to describe how the understanding of fifth grade students of SDN 188 Pekanbaru can be improved through project-based experiments on how the lungs work. This experimental method is designed with an active and contextual learning approach, where students are directly involved in the process of making a lung model using simple tools and materials. The results show that student involvement in experiment based on project capable increase enthusiasm learning and conceptual understanding significantly. In addition, this activity also trains critical thinking skills, teamwork, and scientific communication. These findings underscore the importance of integrating a project-based experimental approach in learning Science. Through activity This, Teacher No only teach theory, but also provide meaningful learning experiences that can improve students' overall learning outcomes.